The Germanic isle : Nazi perceptions of Britain - Strobl, Gerwin (Cambridge Univ. Press, 2000)
"This book explains Hitler's view of Britain as both Nordic ally and role model, and shows that there was a suprising level of affection for Britain and British culture among ordinary Germans, from the discourses of the 1920s to the vigorous anti-British propaganda of the war years. The book includes a number of illustrations, most of which will be unfamiliar to modern readers."--BOOK JACKET.